Need Analysis of English Learning Application based on Muslim Digital Literacy Generation Z at PTKI Metro Lampung - Wiwied Pratiwi; Haikal (CV. Creative Tugu Pena, 2024)
English learning tends to be classic, which focuses more on lecture and textbook methods. The aim of this research was to analyze the need for using English learning applications for the digital literacy of Generation Z Muslims at PTKI Metro Lampung. This research method used qualitative with a collection method using a questionnaire. This research involved 3 lecturers and 90 students in the English Language Education Study Program. The research locations at PTKI Metro Lampung: Universitas Ma'arif Lampung IAIN Metro Lampung and Universitas An Nur Lampung. The results shows that the use interactive English learning application (Lingual Idea) based on generation Z Muslims can support students in learning English. Students need in three language skills with material that has an Islamic nuance (integrating the religious moderation value). and taught digitally, obtained a positive response from students. The development of the English learning application developed on the basis of Gen Z digital literacy which is integrated with the values ​​of religious moderation